Novel Mutations in the DYNC1H1 Tail Domain Refine the Genetic and Clinical Spectrum of Dyneinopathies. Issue 3 (March 2015) - Peeters, Kristien; Bervoets, Sven; Chamova, Teodora; Litvinenko, Ivan; De Vriendt, Els; Bichev, Stoyan; Kancheva, Dahlia; Mitev, Vanyo; Kennerson, Marina; Timmerman, Vincent; De Jonghe, Peter; Tournev, Ivailo; et al.
<x xml:space="preserve">Abstract</x> In this report, we have enriched the spectrum of mutations in the DYNC1H1 gene and their clinical manifestation. We demonstrate that dyneinopathies can present as an axonal form of peripheral neuropathy or a severe motoneuron disorder characterized by multiple congenital contractures and delayed motor milestones, without brain malformations. We provide experimental evidences that molecular defects in DYNC1H1 increase the interaction with its adaptor BICD2. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>